Assortative Mating by Ethnicity in Longevous Families - Sebastiani, Paola; Gurinovich, Anastasia; Bae, Harold; Andersen, Stacy L.; Perls, Thomas T. (Frontiers in Genetics, 2017)
Recent work shows strong evidence of ancestry-based assortative mating in spouse pairs of the older generation of the Framingham Heart Study. Here, we extend this analysis to two studies of human longevity: the Long Life Family Study, and the New England Centenarian Study. In the Long Life Family Study, we identified 890 spouse pairs spanning two generations, while in the New England Centenarian Study we used data from 102 spouse pairs including offspring of centenarians. We used principal components of genome-wide genotype data to demonstrated strong evidence of ancestry-based assortative mating in spouse pairs of the older generation and also confirm the decreasing trend of endogamy in more recent generations. These findings in studies of human longevity suggest that spouses marrying into longevous families may not be powerful controls for genetic association studies, and that there may be important ethnicity-specific, genetic influences and/or gene-environment interactions that influence extreme survival in old generations. In addition, the decreasing trend of genetic similarity of more recent generations might have ramifications for the incidence of homozygous rare variants necessary for survival to the most extreme ages..